The Immobility Turn Mobility, Migration and the COVID-19 Pandemic - Cairns, D.; Clemente, M. (2023)
This book looks at the changes that have taken place in the wake of the COVID-19 pandemic, following the lockdown of societies and imposition of border controls in an attempt to limit the spread of the virus. Using empirical evidence from Portugal, a geopolitically important point of intersection within Europe and between Global South and Global North, the book examines consequences of the apparent end of mobility expansionism, developing a refreshing theoretical concept of ‘immobility turn.’ Focusing on the tourist industry, universities hosting international students and migration agencies, the book offers invaluable insights about how the pandemic affected institutions and individuals’ lives, informing policy-making processes on a global level.